Knee posture during gait and global functioning post-stroke: a theoretical ICF framework using current measures in stroke rehabilitation. (May 2015) - Rosa, Marlene Cristina Neves; Marques, Alda; Demain, Sara; Metcalf, Cheryl D.
Abstract Purpose: To characterise the global functioning post-stroke in patients with normal knee posture (NKP) and abnormal knee posture (AKP) during loading-response. Methods: 35 people, 6 months post-stroke. with NKP and AKP were identified and assessed using clinical measures classified into the corresponding International Classification of Functioning, Disability and Health (ICF) domains: weight function (body mass index); muscle power (knee isometric strength); muscle tone (Modified Ashworth Scale); voluntary motor control (Leg sub-score of Fugl–Meyer scale); walking short distances (5-meter walk test; Timed-Up and Go test); walking on different surfaces (Functional Ambulation Categories); moving around (Falls Efficacy Scale); moving using equipment (walking aids) and global assessment of function (WHODAS II). Age, gender, marital status, current occupation and caregivers support characterised personal factors. Results: Patients with AKP had significantly lower knee flexor strength, higher knee flexor and extensor spasticity, more difficulty in maintaining a standing position, walking short and long distances, used walking aids more often and needed more caregiver support. Restriction in activities and participation were correlated with knee flexor strength for AKP and with knee spasticity for NKP group. Conclusions: AKP restricts functioning and participation. Implications for Rehabilitation Identification of abnormal knee posture in gait can indicate potential assessment and treatment priorities, e.g. knee flexor strength is a major determinant of functioning in patients with abnormal knee posture and should be assessed. The identification of an abnormal knee posture post-stroke seems relevant for planning patient's long-term needs (e.g. amount of caregiver support). The interpretation of functional measures based on the ICF framework can enhance clinical-reasoning in rehabilitation post-stroke.